Spatial Variation of Protected Agriculture (Greenhouses) in Salah al-Din Governorate - Marei, Alaa Fayeq; Abd AlRazzaq, Mathil Arif (Journal of Tikrit University for Humanities, 2024)
The research aims to know the spatial variation of protected agriculture in Salah al-Din for the year 2022, using a special questionnaire to know the geographical distribution of the numbers of plastic houses and tunnels present in the study area, such as the numerical and relative distribution. The study area is located in the northern central part of Iraq, between two latitudes (3327) north from its southern side. The latitude is (35.41) north on its northern side and between longitudes (42.32) east on its western side and (44.59) east on its eastern side. The results of the research showed that two methods of covered agriculture are used in the study area: houses and plastic tunnels. The total number of houses is the number of plastic tunnels in the study area reached (3810) plastic houses, and Dujail District leads as the most district in the study area in possession of plastic houses, with a percentage of (53.15%), while the number of plastic tunnels in the study area reached (4,972,390) tunnels, and Dujail District leads as the most districts in possession of tunnels with a percentage of (83.00%). Several types of covered vegetables are also grown in the study area, namely tomatoes, cucumbers, eggplant, trees, and peppers. The tomato crop ranks first in terms of production, with a percentage of (121,718), and the cucumber crop comes in second place in terms of production, with a percentage of (38,794), followed by The eggplant crop ranked third with a percentage of (25237), then the tree crop ranked fourth with a percentage of (14105), then the pepper crop ranked last with a percentage of (13237).